Effectiveness of Anti-Smoking Policies and Public Perceptions in Peshawar, Khyber Pakhtunkhwa, Pakistan - Zeenat Bibi; Nazima Bibi; Bibi Sultania; Farzana Qasim, (Dialogue Social Science Review (DSSR), 2025)
This study investigates the effectiveness of anti-smoking policies and public perceptions in Peshawar, Pakistan. The research examines the level of public awareness regarding anti-smoking policies, the effectiveness of these policies, and changes in smoking behaviors post-implementation. A total of 126 respondents were surveyed, revealing that 67.5% (85) of participants were fully aware of the policies, 21.4% (27) were partially aware, and 11.1% (14) were not aware. Regarding perceptions of the effectiveness of these policies, 39.7% (50) considered them highly effective, 31.7% (40) regarded them as moderately effective, and 28.6% (36) viewed them as ineffective. Additionally, 47.6% (60) of respondents reported a reduction in smoking habits since the policy implementation, while 31.7% (40) reported no change, and 20.6% (26) indicated an increase in smoking. These findings suggest that while there is significant public awareness and some perceived effectiveness of the policies, more targeted efforts are necessary to further reduce smoking prevalence and enhance policy impact in the region.